The Radical Flank Revisited: How Regulatory Discretion Shapes the Effectiveness of Social Activism on Business Outcomes - Grandy, Jake B.; Hiatt, Shon R. (Organization Science, 2024)
Although scholarship has highlighted how stakeholders can influence business outcomes, few studies have examined how simultaneous, different tactics interact to impact firms. Critical to understanding this interaction is the radical flank effect, which asserts that the moderate and radical elements of social activist tactics can interact to either enhance or diminish a movement’s ability to accomplish its goals. However, research is unclear about when and whether the radical flank effect enhances or diminishes activist influence, nor has it empirically analyzed factors that influence the direction of the effect. To address these limitations, we explore one such factor—regulatory agency discretion, or regulators’ flexibility to interpret and implement public policies. Drawing on management and political sociology studies, we argue that discretion affects the salience of regulatory accountability to the public and thereby alters the radical flank effect on business outcomes in regulated markets. We analyze stakeholder opposition to U.S. hydroelectric power facilities from 1987 to 2019. The results show that high discretion enhances the radical flank effect and detrimentally affects business outcomes, whereas low discretion reverses the radical flank effect and favorably affects business outcomes. Funding: This work was supported by the Kauffman Foundation Doctoral Dissertation Fellowship and the Harvard Business School Division of Research. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16104 .